2001
DOI: 10.1128/cdli.8.4.818-821.2001
|View full text |Cite
|
Sign up to set email alerts
|

Viral Load in Breast Milk Correlates with Transmission of Human Cytomegalovirus to Preterm Neonates, but Lactoferrin Concentrations Do Not

Abstract: In vitro, lactoferrin (LF) strongly inhibits human cytomegalovirus (HCMV), which led us to hypothesize that in vivo HCMV might also be inhibited in secretions with high LF concentrations. In breast milk, high viral loads observed as high viral DNA titers tended to coincide with higher LF levels. However, the LF levels did not correlate to virus transmission to preterm infants. The viral load in the transmitting group was highest compared to the nontransmitting group. We conclude that viral load in breast milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…The dynamics of viral reactivation is similar in every lactating mother, irrespective of whether she acts as viral transmitter or non-transmitter. However, the maximum viral load as well as viral genome copy numbers are significantly different between maternal transmitters and non-transmitters (Hamprecht et al, 2003b;Van der Strate et al, 2001). The initial increase in viral load in breast milk during the first 3 weeks postpartum differs also interindividually, but no difference between maternal transmitters and non-transmitters could be found.…”
Section: Unimodal Kinetics Of Hcmv Reactivationmentioning
confidence: 83%
“…The dynamics of viral reactivation is similar in every lactating mother, irrespective of whether she acts as viral transmitter or non-transmitter. However, the maximum viral load as well as viral genome copy numbers are significantly different between maternal transmitters and non-transmitters (Hamprecht et al, 2003b;Van der Strate et al, 2001). The initial increase in viral load in breast milk during the first 3 weeks postpartum differs also interindividually, but no difference between maternal transmitters and non-transmitters could be found.…”
Section: Unimodal Kinetics Of Hcmv Reactivationmentioning
confidence: 83%
“…In other studies, risk factors for transmission were early onset of CMV DNAlactia and virolactia, 8 prolonged viral excretion in breast milk, 14 and higher milk whey viral loads. 14,41 These may suggest that treating breast milk from CMV-seropositive mothers would be necessary only until the infant reaches a certain age or birth weight, after which the risk of symptomatic disease decreases. A better understanding of risk factors for CMV-SLS in VLBW and premature infants may help refining guidelines for feeding breast milk from CMV-seropositive mothers to these infants.…”
Section: Figurementioning
confidence: 99%
“…As already noted, studies in term newborns revealed that HCMV transmission occurred in spite of the presence of maternally derived neutralising antibodies to HCMV, and that there were no differences noted amongst transmitters and nontransmitters with respect to age, race, duration of lactation, duration of HCMV excretion in milk, presence of HCMV-specific IgA antibody, or infectivity titres of virus in milk, as noted by viral culture [14]. However, a more recent examination of the correlation between viral load in breast milk (using quantitative PCR) and transmission to the neonate did reveal a correlation between HCMV viral load and infection of the infant [27]. Interestingly, this study did not identify a relationship between breast milk levels of lactoferrin, an endogenous antimicrobial constituent of breast milk, and prevention of HCMV transmission.…”
Section: Viral/host Factors Modulating Transmission Of Hcmv From Breamentioning
confidence: 67%